Analysis of Humanistic Attitudes and Self Concept Towards Prosocial Student of Regular School Based on Inclusive - Muhammad Rusli (Departement of Mathematics Education, 2023)
The basic principle of inclusive schools is that all children should learn together, wherever possible, regardless of the difficulties or differences they may face. Many factors influence the success and sustainability of inclusive education, one of which is the prosocial behavior of regular students towards children with special needs. Prosocial behavior carried out by regular students towards students with special needs can be influenced by things related to the students' humanistic attitudes and self-concept. This research aims to determine: The simultaneous influence of humanistic attitudes and self-concept on prosocial students in inclusive schools. This study uses a quantitative approach. The number of samples in this study was 90 regular students at the Inpres Maccini Baru state elementary school, from grades IV, V and VI. Research data was obtained through three data collection tools, namely the prosocial behavior scale, humanistic attitude scale, and self-concept scale. The method used to test the hypothesis is the multiple linear regression method. The calculation to detect partial influence is by carrying out the t test, while calculating the simultaneous influence is by using the F test. The results of the research show that partially the results obtained show that there is a significant influence of humanistic attitudes on prosocial behavior (sig. 0.000 < 0.05). Meanwhile, self-concept does not have a significant influence on prosocial behavior (sig. 0.054 > 0.05). Simultaneously, there is an influence between humanistic attitudes and self-concept on students' prosocial behavior in the inclusion class at SD Negeri Inpres Maccini Baru (p= 0.000 < 0.05) and F count > F table (65.763 > 3.10). The coefficient of determination (R²) value shows 0.602, so that in this study the humanistic attitude and students' self-concept together have an effective contribution to prosocial behavior of 60.2%.